Analisis Kontribusi Dana Bagi Hasil Pertambangan Umum Mineral dan Batubara terhadap Dana Perimbangan, Pendapatan dan Belanja Daerah (Studi Kasus Kabupaten Penghasil Minerba yang ada di Provinsi Kalimantan Selatan Tahun 2016-2020) - Safitri, Rahmi; Sopiana, Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The purpose of this study is to explore how the role of the Mineral and Coal General Mining Revenue Sharing Fund includes Fixed Contributions (Landrent) and Exploration and Exploitation Contributions (Royalty) to Regional Income, Regional Spending and Balance Fund of South Kalimantan Province Minerba Producing Regency from 2016-2020. This research uses contribution analysis measuring instruments that are quantitative descriptive. The data used is secondary time series data (time series). The results showed that the study of the contribution of Fixed Contributions (Landrent) to the APBD balance fund of all Minerba Producing Regencies in South Kalimantan Province showed a lack of category. On average, the gift of Exploration and Exploitation Contributions (Royalty) to the balance fund and APBD of Minerba Producing Regency in South Kalimantan Province shows that diverse categories tend to be quite good. At the same time, the regency that is very dependent is the Regency.